Potential benefits and risk assessments of using sewage sludge on soil and plants: a review. (10th April 2019) - Ali, Majeed; Ahmed, Talaat; Al-Ghouti, Mohammad A.
Fertiliser potential and pollutant risk for the applied sewage sludge in agricultural activities must be specifically evaluated for each sludge due to the fact that there is variation in the characteristics of sludge's in which they undergo different treatment levels, in addition to the differences in the pollutant nature that is found in the wastewater. Therefore, it is required to treat the sludge before using it as fertiliser to eliminate and remove any harmful materials that can negatively affect the environment, human health, soil, and crops, in which it can be treated through aerobic, anaerobic digestion and thermal treatment process.